The The Influence of Job Demand-Resource (JD-R) model on work engagement among Malaysian Northern Region Public Universities Academics - Siti Balkis Mohamed Ibrahim (STIM LASHARAN JAYA MAKASSAR, 2021)
The purpose of this study was to examine the influence of Job Demand-Resource (JD-R) model level towards work engagement. This study brought insight and new contribution in overall JD-R model by serving Big-Five personality as personal resources. The data were gathered via e-survey from samples of academics (n =132) working in public universities located within Northern Region of Malaysia. Study revealed mixed results where personal resources and workload were significantly influence work engagement while the remaining independent variables (autonomy, social support, performance feedback, and emotional demand) shows not significant to predict work engagement in this study context. Besides, findings generally support past studies and suggest situations in accordance to academics’ pressures. The results and implications of the study are discussed.